Safety profile, pharmacokinetics, and biologic activity of MEDI-563, an anti–IL-5 receptor α antibody, in a phase I study of subjects with mild asthma - Busse, William W.; Katial, Rohit; Gossage, David; Sari, Suha; Wang, Bing; Kolbeck, Roland; Coyle, Anthony J.; Koike, Masamichi; Spitalny, George L.; Kiener, Peter A.; Geba, Gregory P.; Molfino, Nestor A. (Journal of allergy and clinical immunology, 2010)
Increased eosinophil levels have been linked to airway inflammation and asthma exacerbations. IL-5 is responsible for eosinophil differentiation, proliferation, and activation; IL-5 receptors are expressed on eosinophils and their progenitors, and targeting such receptors induces eosinophil apoptosis. To evaluate the safety profile, pharmacokinetics, and pharmacodynamics of MEDI-563, a humanized mAb targeting the IL-5 receptor α chain. Single, escalating, intravenous doses (0.0003-3 mg/kg) of MEDI-563 were administered to subjects with mild atopic asthma (n = 44) over ∼3 to 30 minutes in this open-label study. Pulmonary function, symptom scores, adverse events, MEDI-563 pharmacokinetics, and levels of C-reactive protein (CRP), IL-6, eosinophil cationic protein (ECP), and eosinophils were evaluated. Mean peripheral blood (PB) eosinophil levels decreased in a dose-dependent fashion (baseline ± SD, 0.27 ± 0.2 × 103/μL; 24 hours postdose, 0.01 ± 0.0 × 103/μL); 94.0% of subjects receiving ≥0.03 mg/kg exhibited levels between 0.00 × 103/μL and 0.01 × 103/μL. Eosinopenia lasted at least 8 or 12 weeks with doses of 0.03 to 0.1 and 0.3 to 3 mg/kg, respectively. ECP levels were reduced from 21.4 ± 17.2 μg/L (baseline) to 10.3 ± 7.0 μg/L (24 hours postdose). The most frequently reported adverse events were reduced white blood cell counts (34.1%), nasopharyngitis (27.3%), and increased blood creatine phosphokinase (25.0%). Mean C-reactive protein levels increased ∼5.5-fold at 24 hours postdose but returned to baseline by study end; mean IL-6 levels increased ∼3.9-fold to 4.7-fold at 6 to 12 hours postdose, respectively. Pharmacokinetic activity was dose proportional at doses of 0.03 to 3 mg/kg. Single escalating doses of MEDI-563 had an acceptable safety profile and resulted in marked reduction of PB eosinophil counts within 24 hours after dosing.